IDENTITAS BUDAYA MASYARAKAT BADUY DI TENGAH ARUS GLOBALISASI - Clara Blenzisky Naibaho; Septy Risma Caroline Nainggolan; Agus Iryana (Cahaya Ilmu Bangsa, 2024)
This study delves into how the Baduy people confront global challenges,emphasizing the function of customary law as a binding social tool. A qualitative approach was chosen to deeply understand the social reality of the Baduy community, which is viewed as being shaped by the consciousness of individuals within it. Triangulation from various sources and theories was employed to ensure data accuracy. The research is centered in Kanekes Village, Banten, home to the Baduy community that strongly upholds ancestral traditions. The Baduy people maintain their cultural values through oral traditions and practices passed down through generations, keeping these values alive in a modern context. Within this society, there are two main groups:Outer Baduy and Inner Baduy, each with a distinct approach to modernization. The Outer Baduy are more open and adapt to modern elements within certain limits while preserving traditional values, whereas the Inner Baduy focus more on internal education and community organization, choosing isolation as a means to preserve their unique culture. This research explains the steps of data collection, reduction, presentation, and verification, referring to the framework developed by. Pudjiastuti. Overall, this study provides insights into how the Baduy people maintain their cultural values and identity amidst the dynamics of changing times.